Pain intensity and psychological distress show different associations with interference and lack of life control: A clinical registry-based cohort study of >40,000 chronic pain patients from SQRP - Gerdle, Björn; Dragioti, Elena; Rivano Fischer, Marcelo; Ringqvist, Åsa (Frontiers in Pain Research, 2023)
Background Both chronic pain and depressive and/or anxiety symptoms are associated with negative impacts on daily living, including interference and lack of life control. However, little is known about how pain and psychological distress affect these impacts. Aim The first aim was to assess how pain intensity, psychological distress, and social support interact with interference and lack of life control. A second aim was to investigate whether the strength of these relationships is moderated by the presence or absence of depression and/or anxiety. Subjects and methods Patient-Reported Outcome Measures (PROMs), which are available in the Swedish Quality Registry for Pain Rehabilitation (SQRP), were retrieved for patients with chronic pain (N = 40,184). A theoretical model with the constructs/latent variables pain intensity, psychological distress, interference, lack of life control, and social support was proposed and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Indicators for these constructs were identified from the PROMs of the SQRP. Two models of the total cohort, which differed with respect to the causal relationship between pain intensity and psychological distress, were investigated. The moderating effects of anxiety and/or depression were also analyzed. Results Relatively low correlation and explanatory power (R2 = 0.16) were found for the pain intensity-psychological distress relationship. Pain intensity had a stronger effect on interference than on lack of life control. The reverse was found for psychological distress – i.e., psychological distress seemed to have a higher negative influence on function than on interference. The underlying assumption of the causal relationship between pain intensity and psychological distress determined how strong pain intensity and psychological distress influenced interference and lack of life control. Social support showed very similar absolute significant correlations with interference and lack of life control. Interference and lack of life control showed relatively weak associations. The psychological distress level was a moderating factor for several of the paths investigated. Discussion and conclusion A clinical treatment consequence of the low correlation between pain intensity and psychological distress may be that clinically treating one may not reduce the effect of the other. The relative importance of pain intensity and psychological distress on interference and lack of life control depends on the underlying assumption concerning the pain intensity-psychological distress relationship. Interference and lack of life control showed relatively weak associations, underscoring the need to clinically assess them separately. Social support influenced both impact constructs investigated. The cohort display heterogeneity and thus presence of definite signs of anxiety and/or depression or not was a moderating factor for several of the associations (paths) investigated. The results are important both for the assessments and the design of treatments for patients with chronic pain.